Pembentukan kelompok tani hutan sebagai upaya resolusi konflik melalui konsep pemberdayaan masyarakat di KHDTK Kepau Jaya - Andhika Silva Yunianto; Eko Sutrisno (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Kepau Jaya or specific purpose forest area Kepau Jaya, located in Kepau Jaya Village, Siak Hulu Sub-district, Kampar Regency, intended as an experimental farm of bee feed resources and research of the potensial fiber wood from native species. Based on the geographics, the position of KHDTK Kepau Jaya was bordered of the settlement so that deemed necessary to thing for social empowerment in the managerial things. The citizens are dominant work as a farmer in there which are the migrant community. The current concept of forest management areas still focus on the sectoral egos that can trigger such tenurial conflicts like land occupation. As a preventive effort, through an institutional persuasive approach, the establishment of forest farmer groups has been initiated. This is in line with Minister of Environment and Forestry Regulation No. P.83/MENLHK/ SETJEN/Kum.1/10/2016 about Social Forestry. The concept is making the community in managing KHDTK Kepau Jaya as a conservation partner. Member of forest farmer groups are permitted to enter and managing land in KHDTK areas by implementing agrosylvapastura and agroforestry concept using zonation system. Nowadays, the annual crops were harvested and it can be an alternative source of income household for members of forest farmer groups.